Multi-element metal oxide loaded high-adsorbability fiber self-decontamination composite material and preparation method thereof

Through the self-cleaning composite material of high adsorption fibers loaded with multi-metal oxide, the problems of poor stability and disinfection properties of existing metal oxide cleaning materials are solved, and rapid adsorption and efficient degradation of poisons are achieved. Suitable for the decontamination of nuclear and biochemical events.

CN119392487APending Publication Date: 2025-02-07HUBEI HUAQIANG HIGH TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411541824.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing metal oxide cleaning materials have poor stability, low load and water content that have a great impact on degradation performance, resulting in the degradation performance in air-dry areas.

Method used

The self-cleaning composite material of hyperabsorbent fibers loaded by multi-metal oxide is used to synthesize polymetal oxides through co-precipitation method, and combine with organic polymers and additives, and load them to the hyperabsorbent fibers by curing coating method. superior.

Benefits of technology

It realizes rapid adsorption and efficient degradation of poisons, with the characteristics of stability, high degradation performance, portable and easy to operate, and is suitable for the decontamination of nuclear and biochemical events.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392487A_ABST
    Figure CN119392487A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-element metal oxide loaded high-adsorbability fiber self-decontamination composite material and a preparation method thereof, and belongs to the technical field of fiber composite materials. The preparation method of the self-decontamination composite material comprises the following steps: adding an organic polymer multi-element metal oxide and assistants (a wetting agent, a dispersing agent, an adhesion promoter and the like) into N, N-dimethylformamide, stirring for 12-32 hours to obtain composite material slurry, then coating high-adsorbability fibers with the composite material slurry, putting the high-adsorbability fibers into a drying oven at 80-120 DEG C, and drying for 10-14 hours to obtain the self-decontamination composite material. And naturally cooling to obtain the multi-element metal oxide loaded high-adsorbability fiber self-decontamination composite material. The preparation method is simple and effective, and the obtained material has good stability and flexibility, can realize a self-decontamination function of a poison after rapid adsorption, can be used as a technical reserve for research of novel decontamination materials in the future, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber composite materials, and in particular to a multi-metal oxide-loaded high-adsorbability fiber self-cleaning and disinfecting composite material and a preparation method thereof. Background Art

[0002] In order to better deal with the threat to human life safety brought by nuclear, biological and chemical incidents, higher requirements are put forward for chemical agent decontamination materials. At present, traditional decontamination materials include China's activated white clay, the United States XE-555 disinfection resin, the United States A-200 porous adsorption powder and Canada RSDL type wiping sponge. Among them, activated white clay and A-200 porous adsorption powder are physical adsorption materials with good adsorption effect and can quickly remove toxic agents, but in actual application, the powder loss phenomenon is serious. After decontamination, the decontamination equipment needs to be buried, causing secondary pollution and other problems; XE-555 disinfection resin has a certain disinfection ability, but the efficiency is not high, which limits its practicality. On the other hand, the decontamination process of traditional decontamination equipment is relatively complicated and needs to be prepared with water before it can be used.

[0003] Adsorption-reaction type disinfection materials are an important type of disinfection materials. The latest M100 and FAST-ACT developed in the United States use single or composite nano-metal oxides, which have excellent adsorption and disinfection properties, especially composite nano-metal oxides, which have a larger specific surface area and can provide more active sites. However, single metal oxide powders are easy to agglomerate, resulting in reduced adsorption performance, a large impact of water content on degradation performance, and reduced disinfection performance in dry air areas. The commonly used method is to compound metal oxides with fiber materials to further increase their specific surface area and increase reactive sites, but there are also problems such as poor stability and low load of metal oxides. Therefore, under the premise of ensuring that the preparation method is simple and effective, developing an environmentally friendly metal oxide disinfection composite material that takes into account stability and excellent degradation performance is one of the key research directions in the future. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a green and safe metal oxide disinfection composite material having both stability and excellent degradation performance and a preparation method thereof.

[0005] In order to solve the above technical problems, the present invention provides a multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material, comprising: Organic polymers, as the main material of the resin formula, include one or more materials such as polyvinyl pyrrolidone (PVP), polyvinylidene chloride (PVDF), acrylic resin, etc. When only acrylic resin is contained, the effect will be slightly worse.

[0006] The multi-metal oxide has a certain adsorption capacity and can provide active sites for the captured toxic agent molecules, converting the toxic agent molecules into non-toxic substances to achieve the function of self-disinfection. In the preferred scheme of some embodiments, it includes one of the materials such as titanium-manganese-zinc ternary metal oxide, zinc-aluminum-nickel ternary metal oxide, etc.

[0007] The additives are used to evenly distribute the multi-metal oxides on the fibers, giving the highly adsorbent fiber self-cleaning composite material good stability and flexibility, including anionic wetting agents, anionic dispersants, silicone defoaming agents, thickeners, and silane coupling agent adhesion promoters.

[0008] Highly adsorbent fibers have the characteristics of rapid adsorption and high specific surface area, including one of activated carbon fibers or carbon-doped fibers.

[0009] A multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material and a preparation method thereof of the present invention are as follows: Step 1: Synthesis of multi-metal oxides: Using the coprecipitation method, first prepare a metal salt solution, then prepare a precipitant solution by mixing hydrogen peroxide and ammonia water, and finally add the metal salt solution dropwise to the precipitant solution, stir for 1-2 hours at 35°C to 60°C, filter the precipitate, wash it 2-3 times, and transfer it to a muffle furnace for calcination to obtain the multi-metal oxide.

[0010] Step 2: Prepare composite material slurry. Add the organic polymer to DMF and stir for 12-32 hours until the slurry is colorless and transparent to obtain the organic polymer slurry. Then add the multi-metal oxide and the additive to the organic polymer slurry and stir to obtain the composite material slurry.

[0011] Step 3: Curing and coating: Fix one end of the high-absorbency fiber, take the composite material slurry and evenly coat it on the surface of the high-absorbency fiber, then place it in an oven at 80℃~120℃ for 10h~14h, take it out and cool it to room temperature to obtain the high-absorbency fiber self-cleaning and disinfecting composite material.

[0012] In the step 1, the metal salt solution is selected from a combination of any two or more of titanium salts, manganese salts, zinc salts, aluminum salts, nickel salts, and iron salts; the volume ratio of hydrogen peroxide to ammonia water in the precipitant solution is 0.25-1; the solvent for washing the precipitate is selected from any one or two of deionized water, ethanol, and DMF; the temperature for calcining the washed precipitate is 250° C.-400° C., and the calcination time is 12 h-24 h.

[0013] As a further improvement of the present invention, in step 1, the metal salt can be one of titanium salt, manganese salt and zinc salt, zinc salt, aluminum salt and nickel salt, zinc salt, iron salt and nickel salt, wherein the molar ratio of the three metal salts is 1:2:1~3:2:1.

[0014] In some preferred cases, in the step 1, the metal salt solution is selected from a mixture of titanium salt, manganese salt and zinc salt, a mixture of zinc salt, aluminum salt and nickel salt, and a mixture of zinc salt, iron salt and nickel salt to obtain any one mixture, so that it forms a titanium-manganese-zinc ternary metal oxide, a zinc-aluminum-nickel ternary metal oxide, and a zinc-iron-nickel ternary metal oxide material, wherein the molar ratio of the three metal salts is 1:2:1~3:2:1, such as titanium-manganese-zinc ternary metal oxide, the molar ratio of titanium metal salt, manganese metal salt and zinc metal salt is 1:2:1~3:2:1. For example, when it is zinc-aluminum-nickel ternary metal oxide, the molar ratio of zinc metal salt, aluminum metal salt and nickel metal salt is 1:2:1~3:2:1. For example, when it is zinc-iron-nickel ternary metal oxide, the molar ratio of zinc metal salt, iron metal salt and nickel metal salt is 1:2:1~3:2:1.

[0015] In step 2, the organic polymer includes one or more of polyvinyl pyrrolidone (PVP), polyvinylidene chloride (PVDF), and acrylic resin materials.

[0016] As a further improvement of the present invention, in the step 2, the organic polymer may be PVDF, and based on the total weight of the composite material slurry, the content of the organic polymer PVDF is 4% to 65%, the content of the wetting agent in the additive is 0% to 1.0%, the content of the dispersant is 0.5% to 1.5%, the content of the defoaming agent is 0.5% to 1.5%, the content of the thickener is 0% to 1.0%, the content of the adhesion promoter is 1.5% to 2.5%, the content of DMF is 30% to 65%, and the content of the multi-metal oxide is 15% to 45%.

[0017] As a further improvement of the present invention, in the step 2, the organic polymer may be PVP and PVDF, and based on the total weight of the composite material slurry, the total content of the organic polymer is 4% to 65%, the content of the wetting agent in the auxiliary agent is 0% to 1.0%, the content of the dispersant is 0.5% to 1.5%, the content of the defoaming agent is 0.5% to 1.5%, the content of the thickener is 0% to 1.0%, the content of the adhesion promoter is 1.5% to 2.5%, the content of DMF is 30% to 65%, and the content of the multi-metal oxide is 15% to 45%.

[0018] As a further improvement of the present invention, in the step 2, the organic polymer may be acrylic resin, PVP and PVDF. Based on the total weight of the composite material slurry, the total content of the organic polymer is 4% to 65%, the mass ratio of PVP to PVDF is 1 to 4, the wetting agent content in the additive is 0% to 1.0%, the dispersant content is 0.5% to 1.5%, the defoaming agent content is 0.5% to 1.5%, the thickener content is 0% to 1.0%, the adhesion promoter content is 1.5% to 2.5%, the DMF content is 30% to 65%, and the multi-metal oxide content is 15% to 45%.

[0019] The wetting agent includes sodium dodecylbenzene sulfonate; the dispersant is a naphthalene sulfonate dispersant; the defoaming agent is an organic silicon defoaming agent, such as polydimethylsiloxane; the thickener is sodium hydroxymethyl cellulose; and the adhesion promoter is a silane coupling agent, such as KH560.

[0020] As a further improvement of the present invention, in step 3, the high adsorption fiber can be one of activated carbon fiber or activated carbon-based fiber composite material, and its gram weight is 105g / m 2 ~210g / m 2 , with a specific surface area of ​​700m 2 / g~1800m 2 / g.

[0021] Beneficial effects of the present invention: 1. The highly adsorbent fiber self-cleaning and disinfecting composite material loaded with multi-metal oxides of the present invention can achieve rapid adsorption of toxic agents, and the multi-metal oxides on the material can degrade and convert them into low-toxic or non-toxic substances. It is a material that integrates adsorption properties and self-cleaning and disinfecting properties.

[0022] 2. The highly adsorbent fiber self-cleaning composite material loaded with multi-metal oxides of the present invention and its preparation method are simple and effective. The multi-metal oxides are loaded onto the fiber by a curing coating method. It has the characteristics of stability, high degradation performance, portability and easy operation, and has broad application prospects.

[0023] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following specifically cites preferred embodiments and comparative examples, and describes them in detail with the accompanying drawings as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 From left to right in the figure are the physical pictures of the flexibility of the composite materials obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings, specific embodiments and comparative examples so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0026] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0027] Example 1 A multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material and a preparation method thereof, comprising the following steps: Step 1, synthesis of multi-metal oxides. Titanium salt, manganese salt and zinc salt are dissolved in deionized water by coprecipitation method to prepare a metal salt solution, wherein the molar ratio of titanium salt, manganese salt and zinc salt is 1:2:1; hydrogen peroxide and ammonia water are then prepared into a precipitant solution, wherein the volume ratio of hydrogen peroxide to ammonia water is 0.25; finally, the above metal salt solution is added dropwise to the precipitant solution, stirred at 35°C for 2h, the precipitate is filtered, washed twice in water and ethanol, and then transferred to a muffle furnace and calcined at 250°C for 12h to obtain a multi-metal oxide.

[0028] Step 2, prepare composite material slurry. Add organic polymer PVDF to DMF and stir for 12 hours until the slurry is colorless and transparent to obtain organic polymer slurry. Then add multi-metal oxide and auxiliary agent to the organic polymer slurry and stir to obtain composite material slurry, wherein the organic polymer PVDF content is 5% based on the total weight of the composite material slurry, the auxiliary agent contains 0.5% sodium dodecylbenzene sulfonate as a wetting agent, 1% naphthalene sulfonate dispersant, 1% organosilicon defoamer, 0.5% sodium hydroxymethyl cellulose as a thickener, 2% silane coupling adhesion promoter, 60% DMF, and 30% multi-metal oxide.

[0029] Step 3: Curing and coating. Fix one end of the highly adsorbent fiber, take the composite material slurry and evenly coat it on the surface of the activated carbon fiber. After that, place it in an oven at 80°C for 10 hours, take it out and cool it to room temperature to obtain a highly adsorbent fiber self-decontamination composite material. The obtained composite material is tested for decontamination performance and degradation performance.

[0030] According to the test method of GJB 3638A-2020, the residual density of the composite material obtained in Example 1 to the sarin simulant dimethyl methylphosphonate (DMMP) is 1.98 mg / m 2 The degradation rate of DMMP was 85.03% within 5 hours.

[0031] Example 2 A multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material and a preparation method thereof, comprising the following steps: Step 1, synthesis of multi-metal oxides. Zinc salt, aluminum salt and nickel salt are dissolved in deionized water by coprecipitation method to prepare a metal salt solution, wherein the molar ratio of zinc salt, aluminum salt and nickel salt is 2:2:1; then hydrogen peroxide and ammonia water are prepared into a precipitant solution, wherein the volume ratio of hydrogen peroxide and ammonia water is 0.5; finally, the above metal salt solution is added dropwise to the precipitant solution, stirred at 50°C for 2h, the precipitate is filtered, washed twice in water and ethanol, and then transferred to a muffle furnace and calcined at 300°C for 18h to obtain a multi-metal oxide.

[0032] Step 2, prepare composite material slurry. Add organic polymers PVDF and PVP to DMF and stir for 18 hours until the slurry is colorless and transparent to obtain organic polymer slurry. Then add multi-metal oxide and auxiliary agent to the organic polymer slurry and stir to obtain composite material slurry, wherein the organic polymer PVDF content is 1%, the PVP content is 4%, the wetting agent sodium dodecylbenzene sulfonate content in the auxiliary agent is 0.5%, the naphthalene sulfonate dispersant content is 1%, the organosilicon defoamer content is 0.5%, the thickener sodium hydroxymethyl cellulose content is 1%, the silane coupling adhesion promoter content is 2%, the DMF content is 60%, and the multi-metal oxide content is 30%.

[0033] Step 3: Curing and coating. Fix one end of the highly adsorbent fiber, take the composite material slurry and evenly coat it on the surface of the activated carbon fiber. After that, place it in a 100°C oven for 12 hours, take it out and cool it to room temperature to obtain a highly adsorbent fiber self-decontamination composite material. The obtained composite material is tested for decontamination performance and degradation performance.

[0034] According to the test method of GJB 3638A-2020, the residual density of the composite material obtained in Example 2 to the sarin simulant dimethyl methylphosphonate (DMMP) is 2.18 mg / m 2 The degradation rate of DMMP within 5 hours was 93.59%.

[0035] Example 3 A multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material and a preparation method thereof, comprising the following steps: Step 1, synthesis of multi-metal oxides. Zinc salt, iron salt and nickel salt are dissolved in deionized water by coprecipitation method to prepare metal salt solution, wherein the molar ratio of zinc salt, iron salt and nickel salt is 3:2:1; then hydrogen peroxide and ammonia water are prepared into precipitant solution, wherein the volume ratio of hydrogen peroxide and ammonia water is 1; finally, the above metal salt solution is added dropwise to the precipitant solution, stirred at 60°C for 2h, the precipitate is filtered, washed twice in water and ethanol, and then transferred to a muffle furnace and calcined at 400°C for 24h to obtain multi-metal oxides.

[0036] Step 2, prepare composite material slurry. Add organic polymer acrylic resin, PVDF, and PVP to DMF and stir for 24 hours until the slurry is colorless and transparent to obtain organic polymer slurry. Then add multi-metal oxide and auxiliary agent to the organic polymer slurry and stir to obtain composite material slurry, wherein the organic polymer acrylic resin content is 1%, the PVDF content is 0.8%, and the PVP content is 3.2% based on the total weight of the composite material slurry. The auxiliary agent contains 0.5% sodium dodecylbenzene sulfonate as a wetting agent, 1% naphthalene sulfonate dispersant, 0.5% organosilicon defoamer, 1% thickener sodium hydroxymethyl cellulose, 2% silane coupling adhesion promoter, 60% DMF, and 30% multi-metal oxide.

[0037] Step 3: Curing and coating. Fix one end of the highly adsorbent fiber, take the composite material slurry and evenly coat it on the surface of the activated carbon fiber. After that, place it in a 120°C oven for 14 hours, take it out and cool it to room temperature to obtain a highly adsorbent fiber self-decontamination composite material. The obtained composite material is tested for decontamination performance and degradation performance.

[0038] According to the test method of GJB 3638A-2020, the residual density of the composite material obtained in Example 3 to the sarin simulant dimethyl methylphosphonate (DMMP) is 1.48 mg / m 2 The degradation rate of DMMP within 5 hours was 96.89%.

[0039] Comparative Example 1 A multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material and a preparation method thereof, comprising the following steps: Step 1, synthesis of multi-metal oxides. Zinc salt, iron salt and nickel salt are dissolved in deionized water by coprecipitation method to prepare metal salt solution, wherein the molar ratio of zinc salt, iron salt and nickel salt is 3:2:1; then hydrogen peroxide and ammonia water are prepared into precipitant solution, wherein the volume ratio of hydrogen peroxide and ammonia water is 1; finally, the above metal salt solution is added dropwise to the precipitant solution, stirred at 60°C for 2h, the precipitate is filtered, washed twice in water and ethanol, and then transferred to a muffle furnace and calcined at 400°C for 24h to obtain multi-metal oxides.

[0040] Step 2, prepare composite material slurry. Add organic polymer acrylic resin to deionized water and stir for 24 hours until the slurry is colorless and transparent to obtain organic polymer slurry. Then add multi-metal oxide and auxiliary agent to the organic polymer slurry and stir to obtain composite material slurry, wherein the organic polymer acrylic resin content is 5% based on the total weight of the composite material slurry, the auxiliary agent contains 0.5% sodium dodecylbenzene sulfonate as a wetting agent, 1% naphthalene sulfonate dispersant, 0.5% organosilicon defoamer, 1% thickener sodium hydroxymethyl cellulose, 2% silane coupling adhesion promoter, 60% deionized water, and 30% multi-metal oxide.

[0041] Step 3: Curing and coating. Fix one end of the highly adsorbent fiber, take the composite material slurry and evenly coat it on the surface of the activated carbon fiber. After that, place it in a 120°C oven for 14 hours, take it out and cool it to room temperature to obtain a highly adsorbent fiber self-decontamination composite material. The obtained composite material is tested for decontamination performance and degradation performance.

[0042] According to the test method of GJB 3638A-2020, the residual density of the composite material obtained in Comparative Example 1 to the sarin simulant dimethyl methylphosphonate (DMMP) is 8.63 mg / m 2 The degradation rate of DMMP was 30.51% within 8 hours.

[0043] Comparative Example 2 A multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material and a preparation method thereof, comprising the following steps: Step 1, synthesis of multi-metal oxides. Titanium salt and manganese salt are dissolved in deionized water by coprecipitation method to prepare a metal salt solution, wherein the molar ratio of titanium salt to manganese salt is 1:2; hydrogen peroxide and ammonia water are then prepared into a precipitant solution, wherein the volume ratio of hydrogen peroxide to ammonia water is 0.5; finally, the above metal salt solution is added dropwise to the precipitant solution, stirred at 40°C for 2h, the precipitate is filtered, washed twice in water and ethanol, and then transferred to a muffle furnace and calcined at 400°C for 18h to obtain a multi-metal oxide.

[0044] Step 2, prepare composite material slurry. Add organic polymer acrylic resin to deionized water and stir for 24 hours until the slurry is colorless and transparent to obtain organic polymer slurry. Then add multi-metal oxide and auxiliary agent to the organic polymer slurry and stir to obtain composite material slurry, wherein the organic polymer acrylic resin content is 5% based on the total weight of the composite material slurry, the auxiliary agent contains 0.5% sodium dodecylbenzene sulfonate as a wetting agent, 1% naphthalene sulfonate dispersant, 0.5% organosilicon defoamer, 1% thickener sodium hydroxymethyl cellulose, 2% silane coupling adhesion promoter, 60% deionized water, and 30% multi-metal oxide.

[0045] Step 3: Curing and coating. Fix one end of the highly adsorbent fiber, take the composite material slurry and evenly coat it on the surface of the activated carbon fiber. After that, place it in an oven at 80°C for 10 hours, take it out and cool it to room temperature to obtain a highly adsorbent fiber self-decontamination composite material. The obtained composite material is tested for decontamination performance and degradation performance.

[0046] According to the test method of GJB 3638A-2020, the residual density of the composite material obtained in Comparative Example 2 to the sarin simulant dimethyl methylphosphonate (DMMP) is 18.81 mg / m 2 The degradation rate of DMMP was 21.23% within 8 hours.

[0047] Comparative Example 3 A multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material and a preparation method thereof, comprising the following steps: Step 1, synthesis of multi-metal oxides. A coprecipitation method is used to dissolve magnesium salt, cobalt salt and zinc salt in deionized water to prepare a metal salt solution, wherein the molar ratio of magnesium salt, cobalt salt and zinc salt is 1:2:1; hydrogen peroxide and ammonia water are then prepared into a precipitant solution, wherein the volume ratio of hydrogen peroxide to ammonia water is 0.25; finally, the above metal salt solution is added dropwise to the precipitant solution, stirred at 35°C for 2h, the precipitate is filtered, washed twice in water and ethanol, and then transferred to a muffle furnace and calcined at 250°C for 12h to obtain a multi-metal oxide.

[0048] Step 2, prepare composite material slurry. Add organic polymer PVDF to DMF and stir for 12 hours until the slurry is colorless and transparent to obtain organic polymer slurry. Then add multi-metal oxide and auxiliary agent to the organic polymer slurry and stir to obtain composite material slurry, wherein the organic polymer PVDF content is 5% based on the total weight of the composite material slurry, the auxiliary agent contains 0.5% sodium dodecylbenzene sulfonate as a wetting agent, 1% naphthalene sulfonate dispersant, 1% organosilicon defoamer, 0.5% sodium hydroxymethyl cellulose as a thickener, 2% silane coupling adhesion promoter, 60% DMF, and 30% multi-metal oxide.

[0049] Step 3: Curing and coating. Fix one end of the highly adsorbent fiber, take the composite material slurry and evenly coat it on the surface of the activated carbon fiber. After that, place it in a 100°C oven for 12 hours, take it out and cool it to room temperature to obtain a highly adsorbent fiber self-decontamination composite material. The obtained composite material is tested for decontamination performance and degradation performance.

[0050] According to the test method of GJB 3638A-2020, the residual density of the composite material obtained in Comparative Example 3 to the sarin simulant dimethyl methylphosphonate (DMMP) is 15.78 mg / m 2 The degradation rate of DMMP within 8 hours was 74.37%.

[0051] The above embodiments and comparative examples are only preferred examples for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing a highly adsorbent fiber self-cleaning composite material loaded with multi-metal oxides, characterized in that: The preparation method steps are as follows: Step 1: Synthesis of multi-metal oxides by coprecipitation method: firstly, a metal salt solution is prepared, then hydrogen peroxide and ammonia water are prepared into a precipitant solution, and finally the metal salt solution is added dropwise into the precipitant solution, and after stirring, the precipitate is filtered, washed, and calcined to obtain the multi-metal oxides; Step 2: preparing composite material slurry, adding organic polymer into DMF and fully stirring to obtain organic polymer slurry, then adding multi-metal oxide and additive into the organic polymer slurry and fully stirring to obtain composite material slurry; Step three, curing coating, fix one end of the high-absorbency fiber, take the composite material slurry and evenly coat it on the surface of the high-absorbency fiber. After completion, place it at 80℃~120℃ to react for 10h~14h, take it out and cool it to room temperature to obtain a high-absorbency fiber self-cleaning and disinfecting composite material.

2. The method for preparing the multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material according to claim 1, characterized in that: In the step 1, the metal salt solution is selected from a combination of any two or more of titanium salts, manganese salts, zinc salts, aluminum salts, nickel salts, and iron salts; the volume ratio of hydrogen peroxide to ammonia water in the precipitant solution is 0.25-1; the solvent for washing the precipitate is selected from any one or two of deionized water, ethanol, and DMF; the temperature for calcining the washed precipitate is 250° C.-400° C., and the calcination time is 12 h-24 h.

3. The method for preparing the multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material according to claim 2, characterized in that: In the step 1, the metal salt solution is selected from a mixture of titanium salt, manganese salt and zinc salt, a mixture of zinc salt, aluminum salt and nickel salt, and a mixture of zinc salt, iron salt and nickel salt to obtain any one of the mixtures, so as to form a titanium-manganese-zinc ternary metal oxide, a zinc-aluminum-nickel ternary metal oxide, or a zinc-iron-nickel ternary metal oxide material.

4. The method for preparing the multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material according to claim 2, characterized in that: In step 2, the organic polymer includes one or more of polyvinyl pyrrolidone (PVP), polyvinylidene chloride (PVDF), and acrylic resin materials.

5. The method for preparing the multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material according to claim 1, characterized in that: The organic polymer is PVDF. Based on the total weight of the composite material slurry, the content of the organic polymer PVDF is 4% to 65%. The additive contains 0% to 1.0% wetting agent, 0.5% to 1.5% dispersant, 0.5% to 1.5% defoamer, 0% to 1.0% thickener, 1.5% to 2.5% adhesion promoter, 30% to 65% DMF, and 15% to 45% multi-metal oxide.

6. The method for preparing the multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material according to claim 1, characterized in that: In step 2, the organic polymer can also be PVP and PVDF. Based on the total weight of the composite material slurry, the total content of the organic polymer is 4% to 65%, the content of the wetting agent in the auxiliary agent is 0% to 1.0%, the dispersant is 0.5% to 1.5%, the defoaming agent is 0.5% to 1.5%, the thickener is 0% to 1.0%, the adhesion promoter is 1.5% to 2.5%, the DMF content is 30% to 65%, and the content of the multi-metal oxide is 15% to 45%.

7. The method for preparing the multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material according to claim 6, characterized in that: In step 2, the organic polymer can also be acrylic resin, PVP and PVDF. Based on the total weight of the composite material slurry, the total content of the organic polymer is 4% to 65%, the mass ratio of PVP to PVDF is 1 to 4, the wetting agent content in the auxiliary agent is 0% to 1.0%, the dispersant content is 0.5% to 1.5%, the defoaming agent content is 0.5% to 1.5%, the thickener content is 0% to 1.0%, the adhesion promoter content is 1.5% to 2.5%, the DMF content is 30% to 65%, and the multi-metal oxide content is 15% to 45%.

8. The method for preparing the multi-metal oxide-loaded high-adsorbability fiber self-cleaning composite material according to claim 7, characterized in that: In step 3, the highly absorbent fiber is one of activated carbon fiber or carbon-doped fiber, and its gram weight is 105 g / m 2 ~210g / m 2 , with a specific surface area of ​​700m 2 / g~1800m 2 / g.

9. A highly adsorbent fiber self-cleaning composite material loaded with multi-metal oxides, characterized in that: A composite material prepared by the method according to any one of claims 1 to 9.

10. Use of the highly adsorbent fiber self-cleaning composite material loaded with multi-metal oxides according to claim 9 in the adsorption and / or degradation of dimethyl methylphosphonate.